A network analysis of academic procrastination, psychological and environmental factors among medical students - Siyu Huang; Zhuo Li; Jianing Li; Xinfang Ding (BMC Psychology)
Abstract Background Academic procrastination is a multifaceted phenomenon influenced by psychological and environmental factors and has potential negative academic and career consequences. However, there are no studies that have comprehensively explored the mechanisms of academic procrastination in medical students. This study conducts a network analysis of seven factors associated with procrastination, to establish a network of academic procrastination, and to explore the academic procrastination network and the relative importance of the different factors. Methods A sample of 681 students (72.1% women, 27.9% men) completed self-rating questionnaires that measured fear, conscientiousness, self-efficacy, impulsivity, depression, the nature of tasks, teacher traits, and academic procrastination. Two networks were created using regularized partial correlation network analysis (EBICglasso) with scales and items as nodes respectively, to determine the role of psychological and external environmental factors in academic procrastination. Results Both networks were linkage active, and all variables showed significant correlations. Impulsivity and depression emerged as the central and bridge components, with the highest centrality indices observed for difficulty concentrating and self-hatred. Environmental factors have the highest expected influence value in the Scale-level network and academic procrastination. Conclusion The present study shows that impulsivity and depression are key factors in academic procrastination networks in the medical student population, especially difficulty concentrating and self-hatred. It further adds the influential role played by environmental factors. Trial registration This is an observational study based on surveys and network analysis, and no healthcare intervention was involved. Therefore, it was not registered in any clinical trial registry.